Analisis Kebutuhan Pengembangan Model Pembelajaran Trikaya Parisudha di Sekolah Dasar - I Gede Astawan (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2020)
This study aims to analyze the needs as a basic of the trikaya parisudha learning model development in primary school to improve students’ science process skills and character values. This research used survey method. The populations of this research are the principals, teachers, and fourth grade students in primary schools which implement Curriculum 2013 in Karangasem Regency, Bali. The sample was determined by using purposive sampling technique, determine 6 primary schools, along with the principals, 12 teachers, and 120 students. The data were collected by using questionnaires, observation, and interview. The data were analyzed descriptively. The result shows that the development of Trikaya Parisudha learning model is needed in order to increase students’ science process skills and character values.   Penelitian ini bertujuan untuk menganalisis kebutuhan sebagai dasar pengembangan model pembelajaran trikaya parisudha di sekolah dasar untuk peningkatan keterampilan proses sains dan nilai-nilai karakter siswa. Penelitian ini menggunakan metode survei. Populasi penelitian adalah kepala sekolah, guru, dan siswa kelas IV sekolah dasar inti pelaksana Kurikulum 2013 di Kabupaten Karangasem, Bali. Sampel penelitian ditentukan dengan teknik purposive sampling, diperoleh 6 sekolah dasar, beserta kepala sekolahnya, 12 guru, dan 120 siswa. Data dikumpulkan dengan angket, observasi, dan wawancara. Data dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa pengembangan model pembelajaran trikaya parisudha sangat dibutuhkan untuk peningkatan keterampilan proses sains dan nilai-nilai karakter siswa.